DIGITAL PROFICIENCY AMONG LIS POSTGRADUATE STUDENTS: AWARENESS AND USAGE OF ADVANCED TECHNOLOGIES AND SOFTWARE TOOLS IN KARNATAKA UNIVERSITIES - G., Manjunatha; B. T. Sampath Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the awareness and use of various technological tools, including data compression tools, statistical software, web design software, plagiarism detection software, virtual meeting platform tools and advanced technologies among LIS postgraduate students in universities across Karnataka state. A structured questionnaire used for data collection and personally distributed questionnaire to students at selected universities. A total of 153 duly filled questionnaires were received from LIS students. The study highlights the levels of awareness and use of software among LIS students. WinZip and WinRAR are identified as the frequently used data compression tools. Additionally, the study found that the highest number of female students were enrolled in LIS programs. The findings suggest that advanced technologies should be included in the LIS curriculum. Students should regularly share their feedback on the curriculum, this feedback can help make improvements and keep the curriculum useful and up to date.